Comprehensive positional and morphological assessments of the temporomandibular joint in adolescents with skeletal Class III malocclusion: a retrospective CBCT study - Yanxi Chen; Lingfeng Li; Ying Li; Nan Luo; Hongwei Dai; Jianping Zhou (BMC, 2023)
Abstract Background Condyle-fossa relationships in adolescents with skeletal Class III malocclusion remain unclear. Therefore, this study used cone-beam computed tomography (CBCT) to evaluate the position and morphology of the temporomandibular joint (TMJ) in adolescents with skeletal Class III malocclusion. Methods In this cross-sectional retrospective study, CBCT images from 90 adolescents with skeletal Class III malocclusion and 30 controls were analysed. Adolescents with skeletal Class III malocclusion were divided into different groups based on (1) sex (male and female), (2) sides (right and left), (3) age (early, middle, and late adolescence), and (4) vertical skeletal patterns (hyperdivergent, normodivergent, and hypodivergent). Morphology of the condyle and fossa as well as condylar position, was compared among groups. Data were collected and submitted for statistical analysis. This study adheres to STROBE guidelines. Results Regarding the intergroup comparisons, there were significant differences in TMJ position and morphology between the skeletal Class III malocclusion with different vertical skeletal patterns and control groups (P < 0.05). Within groups, condyle-fossa relationships differed significantly according to sex, age, and vertical skeletal patterns (P < 0.05); however, the mean values were not statistically different between left and right sides in adolescents with skeletal Class III malocclusion. Conclusions Our findings can be used clinically and radiographically to evaluate the condyle and glenoid fossa features in adolescents with skeletal Class III malocclusion, providing a basis for better TMD diagnosis and orthodontic treatment.